Monitored epidural catheter placement–ultrasound-guided neurostimulation-aided thoracic catheter placement via caudal route for perioperative analgesia in neonatal thoracotomies: A technical feasibility study - Sandeep Diwan; Divya Sethi; Sudhakar Jadhav; Santosh Patil (Indian Journal of Anaesthesia, 2023)
In this case series, we investigated the feasibility of combining ultrasound and neurostimulation for inserting a stimulating epidural catheter in the thoracic epidural space through the caudal route in neonates. Twelve neonates undergoing tracheo-oesophageal fistula repair under general anaesthesia were studied. The catheter was visible on ultrasound as a hyperechoic dot in the epidural space. Inadvertent high placement was identified in two neonates with neurostimulation, in whom the catheter was withdrawn to the thoracic epidural space, and the position was confirmed on ultrasound. A 0.5 ml/kg bolus dose of 0.125% bupivacaine injected through the epidural catheter was imaged in real-time in the epidural space. Block was effective in 10 neonates; two needed an additional local anaesthetic (LA) bolus. To conclude, ultrasound with neurostimulation facilitates accurate positioning of the caudally placed epidural catheter to the mid-thoracic level in neonates.